Analisis Capaian Fisika Dasar Mahasiswa Teknik Geologi: Perspektif Beban Kognitif, Penalaran Spasial, dan Gender dalam Pembelajaran Geosains - I Made Hermanto; Moch. Rio Pambudi; Ni Luh Sri Maharani (Universitas Negeri Gorontalo, 2025)
Introductory Physics plays a fundamental role in Geological Engineering education, as it supports the modeling of dynamic and multidimensional Earth system phenomena. Nevertheless, the course is often perceived as challenging due to the complex integration of conceptual understanding, mathematical reasoning, and multiple representations. This study aims to analyze patterns of academic achievement in Introductory Physics among Geological Engineering students and to explore potential gender-based differences. A descriptive quantitative design with an exploratory comparative approach was employed involving 24 students enrolled in the 2025/2026 academic year. Data were derived from Midterm Examination scores covering quantities and measurement, kinematics, dynamics, and work–energy. Descriptive analysis revealed a moderate level of overall achievement (63.1%) with substantial variability across students. Dynamics and Work–Energy emerged as the most challenging topics compared to quantities and measurement. These findings are associated with high intrinsic cognitive load and substantial spatial reasoning demands required in these domains. Comparative analysis indicated a statistically significant gender difference (p 0.05) with a large effect size, although the finding remains context-specific. The results underscore the need for strengthened representational scaffolding, improved conceptual integration of energy principles, and explicit spatial reasoning support in Introductory Physics curricula for geoscience education.